Prophylactic Use of Tranexamic Acid in Reducing Blood Loss and Preventing Postpartum Haemorrhage in Elective Caesarean Section - Samreen Akram , Sadaf Asma , Sidra Tul Muntaha , Farhan Hassan , Sara Hayat , Rafiq Ahmed (Journal of Islamic International Medical College, 2023)
Objective: To compare the mean blood loss in women administered pre-operative prophylactic tranexamic acid versus control group undergoing elective lower segment caesarean section. Study Design: It was an experimental study. Place and Duration of Study: Study was carried out at Department of Obstetrics and Gynecology at Federal Government Polyclinic Hospital Islamabad from 9 Mar 2021 to 8 Sep 2021. Materials and Methods: A total of 100 patients were selected who were presented for elective cesarean delivery under spinal anesthesia. Women were equally divided into two groups A & B with 50 patients in each group. Patients in group A were preoperatively given 1gm of tranexamic acid intravenously. Group B did not receive tranexamic acid. Immediately after delivery of neonate both groups received 10 units of oxytocin. All abdominal sponges, gauzes, pads were weighed before surgery and postoperatively and blood from suction container also measured in ml. Postoperatively per vaginal bleeding up to 24 hours were measured by total number of pads used, weighed for dry and wet weight and blood loss measured in ml. Total blood loss was measured. Data analysis was performed through SPSS version 22. Results: The mean age for Group A and Group B was 29.9years±6.51SD and 28.7years ±5.13SD respectively. The mean age for the total study subjects was 29.3 ±5.9SD. The mean and standard deviation for blood loss after elective lower segment caesarean section in Group A was 576.6ml± 91.59SD and in Group B it was 836.6ml±91.59SD respectively with 31 %reduction in blood loss in group A. It is clear from the results that blood loss was significant in both the groups with p-value=0.001. Conclusion: The blood loss is significantly reduced in women undergoing elective lower segment caesarean section by administering pre-operative prophylactic tranexamic acid.